Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (Zenodo, 2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; Björn-CV-OECS; _C:Germany DEU; _COVID-Continuity-Blogpost-01; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence; _yl:p